Skin vascular lesions: A new therapeutic option with sequential laser‐assisted technique. Issue 1 (7th December 2020) - Zerbinati, Nicola; Protasoni, Marina; D'Este, Edoardo; Mocchi, Roberto; Coricciati, Luigi; Rauso, Raffaele; Sbano, Paolo; Greco, Maurizio; Rodighiero, Eleonora; Satolli, Francesca
Abstract: Treatment of skin unaesthetic vascular lesions is still suboptimal. In this article, we present a multicenter study evaluating the efficacy and safety of the sequential 755 nm Alexandrite and 1064 nm ND:YAG lasers for the treatment of acquired and congenital vascular lesions of the skin. A total of 171 patients were included in the study (141 female and 30 male), median age 38, skin type from I to IV. Numbers of patients categorized for treated disease: 22 spider angiomas, 67 facial telangiectasia/spider veins, 58 leg telangiectasia/reticular leg veins, 24 port wine stains (PWS). Of those lesions 30.7% was on legs, 63.7% on face (6.7% on forehead, 10.1% on temples, 21.7% on cheeks, 25.2% on nose, 1.7% on chin) and 5.6% on chest. Spider angiomas required from 1 to 3 treatments. Facial telangiectasias had been treated from 1 to 4 times. Leg telangiectasias needed from 2 to 6 treatment sessions. Regarding PWS, it takes from 6 to 9 laser treatment to reach the clearance of the lesion. All the vascular disorders treated showed marked improvement while side effects were limited to low pain sensation and transitory fenomena. This sequential treatment is an effective, safe, and new approach for unaesthetic skin vascular lesions.